Consensus Forecasts and Inefficient Information Aggregation - Crowe, Christopher (IMF Working Papers; Working Paper ;, 2010)
Consensus forecasts are inefficient, over-weighting older information already in the public domain at the expense of new private information, when individual forecasters have different information sets. Using a cross-country panel of growth forecasts and new methodological insights, this paper finds that: consensus forecasts are inefficient as predicted; this is not due to individual forecaster irrationality; forecasters appear unaware of this inefficiency; and a simple adjustment reduces forecast errors by 5 percent. Similar results are found using US nominal GDP forecasts. The paper also discusses the result's implications for users of forecaster surveys and for the literature on information aggregation.